The commentarial transformation of the Spring and Autumn - Van Auken, Newell Ann (State University of New York Press, 2016)
Orthodoxy and transformation: two categories of commentary – The ritual filter and the centrality of Lu – Hierarchy, criticism and commendation: recognizing merit and assigning fault – Two ways of teaching the Spring and Autumn: the sources of the direct commentaries – Other approaches to commentary in the Zuo tradition: the Gentleman and Confucius – The direct commentaries versus Gongyáng and Guliáng: incomplete correspondences and the likelihood of mediated contact – From recording rules to written text: conceptual antecedents to Gongyáng and Guliáng in the direct commentaries – Epilogue: from Zhou Gong to Confucius: textual creation myths forgotten and replaced – Appendix: summaries and topical lists of the direct commentary passages
Includes bibliographical references
Keywords: Zuoqiu; Ming; Confucius; Chun qiu; Zuo zhuan